Improving Student’s Coding Skill with Gamification Website-based Program - Rizal, Rahmat; Susilo, Edi; Nasution, Salhazan (International Journal of Electrical, Energy and Power System Engineering, 2021)
People's dependence on digital technology has increased rapidly since the global Covid-19 pandemic. This causes the world's need for digital products and human resources to make digital products higher. Informatics Engineering Program is one of the providers of human resources who are proficient in the field of information technology. One of the basic skills that must be possessed to create digital products is programming or coding skills. The more skilled a person is at typing and understanding coding, the more complex the digital products he can create. This is why the coding ability of students in the Informatics Engineering Program must be improved. This website-based coding training program aims to improve the coding skills of Informatics Engineering students with interesting and fun gamification methods. Gamification methodology will greatly benefit student of Informatics Engineering Program in Riau University to improve his or her coding skill without consuming too much time and energy.